PRELIMINARY STUDIES OF SEAMLESS FLUX CORED WIRES STORED IN EXTREME CONDITIONS (Metallurgy and Foundry Engineering, 2016)
In the paper preliminary experimental studies of flux cored wires moisturized under controlled conditions are described. Three seamless wires of different grades have been placed in environmental chamber and moisturized in extremely adverse conditions (temperature T = 60° C, relative humidity H = 90%) for 240 hours. During this time measurements of weight gain and observations of surface of wires have been carried out. Also diffusible hydrogen amount in deposited metal has been determined by mercury method for one of moisturized wire. Significant increase of hydrogen level was observed (from H5 to H10 level). Further research will be aimed on determination of the effect of storage conditions on hydrogenation of deposited metal and quality of flux cored wires.